Circadian rhythm disturbances in depression - Germain, Anne; Kupfer, David J. (Human psychopharmacology, 2008)
Objective The aim of this article is to review progress in understanding the mechanisms that underlie circadian and sleep rhythms, and their role in the pathogenesis and treatment of depression. Methods Literature was selected principally by Medline searches, and additional reports were identified based on ongoing research activities in the authors' laboratory. Results Many physiological processes show circadian rhythms of activity. Sleep and waking are the most obvious circadian rhythms in mammals. There is considerable evidence that circadian and sleep disturbances are important in the pathophysiology of mood disorders. Depressed patients often show altered circadian rhythms, sleep disturbances, and diurnal mood variation. Chronotherapies, including bright light exposure, sleep deprivation, and social rhythm therapies, may be useful adjuncts in non‐seasonal and seasonal depression. Antidepressant drugs have marked effects on circadian processes and sleep. Conclusions Recent progress in understanding chronobiological and sleep regulation mechanisms may provide novel insights and avenues into the development of new pharmacological and behavioral treatment strategies for mood disorders. Copyright © 2008 John Wiley & Sons, Ltd.